2022
DOI: 10.1021/acs.analchem.2c02003
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-N-nitrosourea Induced 3′-Glutathionylated DNA-Cleavage Products in Mammalian Cells

Abstract: Apurinic/apyrimidinic (AP) sites, that is, abasic sites, are among the most frequently induced DNA lesions. Spontaneous or DNA glycosylase-mediated β-elimination of the 3′-phosphoryl group can lead to strand cleavages at AP sites to yield a highly reactive, electrophilic 3′-phospho-α,β-unsaturated aldehyde (3′-PUA) remnant. The latter can react with amine or thiol groups of biological small molecules, DNA, and proteins to yield various damaged 3′-end products. Considering its high intracellular concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Notably, Yang and colleagues also showed that the half-life of Schiff base DPCs derived from histone and 3′-pUA ranges from 10 to 14 h in vitro ( 49 ). Overall, our observations of the important role of GSH in forming GSH-adducted SSB and in competing with TFAM in the DPC formation corroborate results from the Gates and Wang laboratories showing the glutathionylation of β-elimination products of AP sites in nDNA ( 30 , 50 ). Additional studies are needed to clarify which type(s) of TFAM-induced DNA modifications are more persistent in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…Notably, Yang and colleagues also showed that the half-life of Schiff base DPCs derived from histone and 3′-pUA ranges from 10 to 14 h in vitro ( 49 ). Overall, our observations of the important role of GSH in forming GSH-adducted SSB and in competing with TFAM in the DPC formation corroborate results from the Gates and Wang laboratories showing the glutathionylation of β-elimination products of AP sites in nDNA ( 30 , 50 ). Additional studies are needed to clarify which type(s) of TFAM-induced DNA modifications are more persistent in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…Organisms constantly undergo subtle genomic changes due to endogenous genotoxins like reactive ROS, ionizing radiation, and environmental alkylating agents. BER pathway primarily handles minor DNA alterations such as single-strand breaks (SSBs) ( 57 ). Initiated by damaged bases, BER excises and replaces them with newly synthesized DNA.…”
Section: The Ercc4 Gene and Its Biological Functionsmentioning
confidence: 99%
“…Similarly, mammalian ERCC1-ERCC4 can remove 3’-phosphoglycolate from DNA’s 3’ end (resulting from oxidative attack) in vitro . Hence, ERCC1-ERCC4 may act as a backup for processing oxidatively damaged DNA in mammalian cells ( 57 59 ).…”
Section: The Ercc4 Gene and Its Biological Functionsmentioning
confidence: 99%
“…Apurinic/apyrimidinic endonuclease1 (APE1) is an essential DNA repair enzyme in human cells, and its aberrant expression is closely linked to the development of cancer. Therefore, APE1 serves as a potential new target for specific cancer types, and its highly sensitive detection holds significant potential for facilitating the early diagnosis of malignant tumors. , Currently, electrochemiluminescence (ECL) technology has emerged as a powerful analytical tool for monitoring various cancer biomarkers in clinical diagnostics due to its low background, broad detection range, and high sensitivity. In recent years, polycyclic aromatic hydrocarbons (PAHs) and their derivatives have become one of the most promising emitters in the field of ECL bioanalysis because of their distinctive optical and electronic properties. , Recently, we used the self-accelerating Ag@Pyc nanocapsules as ECL emitters to achieve sensitive detection of APE1 activity . However, pyrene with a planar structure usually stacks in crystals with strong π–π interactions, resulting in severe internal filtering effects and excessive inactivated emitters, which limits the ECL efficiency of the emitters. ,, Therefore, there is an urgent need to investigate an efficient and convenient strategy to enhance the dispersion of pyrene molecules in order to improve the performance of the ECL biosensor.…”
mentioning
confidence: 99%